Evolution of the Insulin Gene: Changes in Gene Number, Sequence, and Processing - Irwin, David M. (Frontiers in Endocrinology, 2021)
Insulin has not only made major contributions to the field of clinical medicine but has also played central roles in the advancement of fundamental molecular biology, including evolution. Insulin is essential for the health of vertebrate species, yet its function has been modified in species-specific manners. With the advent of genome sequencing, large numbers of insulin coding sequences have been identified in genomes of diverse vertebrates and have revealed unexpected changes in the numbers of genes within genomes and in their sequence of that likely impact biological function. The presence of multiple insulin genes within a genome potentially allows specialization of an insulin gene. Discovery of changes in proteolytic processing suggests that the typical two-chain hormone structure is not necessary for all of inulin’s biological activities.